Feasibility of developing strain-hardening geopolymer composite plates by hot-pressing method. (April 2023) - Cao, Yidong; Ma, Jiaxin; Lin, Chang; Yang, Mengjun; Xu, Shuying; Pan, Lisha
Abstract: Fly-ash-based strain-hardening geopolymer composite (SHGC) plates were manufactured by hot-pressing on a plate vulcanizing press machine. The strain-hardening behavior of SHGC was examined by direct tensile tests, displaying an ultimate strain more than 4%. The flexural behavior of SHGC was investigated by centrally loaded square plates. The parameters under investigation included liquid-to-solid ratio, age, temperature, pressure, fiber type and content. The influence of these parameters on load carrying capacity, deflection, toughness and failure mode were analyzed. The results showed that the load carrying capacity increased with temperature, pressure and age, while the ductility decreased slightly. The specimens gained 66% and 89% load carrying capacity at 1 d and 7 d, respectively, in the reference to that for 28 d. The plates reinforced with 1.5% by volume fiber gave performance comparable to that for 2%. The plates with oiled polyvinyl alcohol (PVA) fibers are around 20% higher than those with non-oiled PVA fibers in maximum load and deflection under flexure. This study has proven the feasibility of fabricating high-ductility SHGC plates by a hot-pressing machine readily available from the market, which could be a preferred option for applications in precasting industry.